PERANCANGAN CORPORATE IDENTITY DAN RE-BRANDING LOGO STUDI KASUS DI W&A BABY SHOP DAN SPA BATANG - Azmi Maulana; Teguh Setiadi; Miftahurrohman (Informatika: Jurnal Teknik Informatika dan Multimedia, 2026)
Corporate identity design plays a crucial role in building brand image and enhancing competitiveness, particularly for micro, small, and medium enterprises (UMKM). W&A Baby Shop and Spa, an umkm based in Batang that provides baby products and spa services, faces challenges in visual identity and promotional strategies. The existing logo lacks appeal, character, and does not effectively reflect the company’s vision, mission, and services. This study aims to redesign the logo and visual identity of W&A Baby Shop and Spa to be more communicative, attractive, and aligned with its brand image, as well as to develop promotional strategies through print and digital media. The research employs the Research and Development (R&D) method consisting of seven stages: problem identification, information gathering, product design, design validation, product revision, user testing, and final revision. The results produce a new logo design that is playful, friendly, and memorable, while supporting promotional activities through various social media platforms. This design is expected to strengthen the brand image of W&A Baby Shop and Spa and increase customer loyalty and engagement.